Woven Voices: Recommendations for Counsellors Working with Professional Interpreters - Amouyal, Mairav A. Z.; Wu, Rosa; Patterson, Pamela (Canadian Journal of Counselling and Psychotherapy, 2020)
This study used the enhanced critical incident technique to examine meaningful incidents that helped, hindered, or were desired by 7 professional interpreters (PI) working in mental health care. Data analysis resulted in 562 critical incidents (CI), 258 helping CIs, 223 hindering CIs, and 81 wish-list items. Counselling and education recommendations are provided, which include PI’s intrapersonal processes; counsellor’s presence, collaboration, and education on PI-mediated sessions; community and government support for PIs; and clients’ understanding of PI-mediation sessions, communication style, family dynamics, and community.